Progression of coronary artery calcification at the crossroads: sign of progression or stabilization of coronary atherosclerosis? - Rodriguez Granillo, Gaston Alfredo (2016)
Coronary artery calcification (CAC) has been strongly established as an independent predictor of adverse events, with a significant incremental prognostic value over traditional risk stratification algorithms. CAC progression has been associated with a higher rate of events. In parallel, several randomized studies and meta-analysis have shown the effectiveness of statins to slow progression and even promote plaque regression. However, evidence regarding the effect of routine medical therapy on CAC has yielded conflicting results, with initial studies showing significant CAC regression, and contemporaneous data showing rather the opposite. Accordingly, there is currently a great controversy on whether progression of CAC is a sign of progression or stabilization of coronary artery disease (CAD). The finding of inexorable CAC progression despite the implementation of intensive contemporaneous medical therapy suggests that further understanding of this phenomenon should be undertaken before the implementation of CAC as a surrogate endpoint for longitudinal studies, or for prospective follow-up of patients under routine medical treatment.